LoRaWAN-Based Automated Waste Bin Monitoring System Using the Antares Platform - Ardi Prabowo, Muhamad Cahyo; Kusumastuti, Sri; Supriyati, Supriyati; A J, Atikah; Rosita C., Erie; A. Santoso, Muhammad (Emitor: Jurnal Teknik Elektro, 2025)
The problem of waste in densely populated areas is a serious challenge that requires systematic and sustainable handling. The formulation of the problem in this study is how to design and build an automatic waste bin monitoring system based on LoRaWAN that has the ability to send data in real-time to the Antares platform. This study aims to design and build an automatic waste bin monitoring system that is able to provide information using the LoraWan architecture with the Antares platform. This system uses a number of ultrasonic sensors to detect waste volume and a number of limit switches to monitor the position of the trash bin lid. The LoRa module is used as a long-distance wireless data communication medium, while the Antares platform acts as a cloud-based data storage and presenter that can be accessed via a web dashboard. The system prototype was tested under various conditions. The aim is to evaluate sensor reliability, data transmission stability, and efficiency in power usage. The test results can monitor with a percentage of successful data transmission of 68% and experience errors or failures of 32%. In short, this monitoring system can be an efficient solution in supporting intelligent waste management based on the Internet of Things (IoT) and is fully feasible to be implemented in urban environments as part of the implementation of the smart city concept.